FEATURES OF HEART RATE REGULATION IN ADOLESCENTS WITH ESSENTIAL HYPERTENSION - A. M. Valeeva; O. V. Sorokin; Zh. N. Nefedova; V. G. Kaynara; L. M. Panasenko; L. P. Deryagina; N. P. Kareva (Сибирский научный медицинский журнал, 2019)
Cardiointervalography is an important method of analyzing the regulation of heart rate variability, which allows evaluating the balance of the entire spectrum of humoral-metabolic and vegetative effects, both in condition of physiological rest and in various functional tests. It is noted that in hypertensive patients, in most cases, there is a chronic predominance of ergotrophic metabolic reactions that reflect the system tension in the regulatory mechanisms. The aim of our study was to conduct a comparative analysis of the features of the mechanisms of heart rate regulation in adolescents with confirmed essential hypertension and their healthy age mates. Material and methods. The study involved 50 adolescents (12–16 years of age) – 26 boys and 24 girls with labile essential hypertension (EHT) and stage 1 HT on the background of the standard medical correction of blood pressure (enalapril 0,58 mg/kg per day). Each participant of the study and control group underwent recording of at least 512 cardio cycles in the state of physiological rest in a sitting position, as well as registration of blood pressure. Results and discussion. We have found that for adolescents with EHT a significantly lower (by 15 %) average duration of the heart cycle is typical in combination with a decrease in the variation range, which indicates some rigidity of the heart rate regulatory mechanisms. The relative decrease in the proportion of high-frequency spectrum components in comparison with the low-frequency and very low-frequency ranges in adolescents with hypertension also indicated a tendency to predominance of sympathicotonic effects with the predominant involvement of the structures of the diencephalic region and the brain stem. At the same time blood pressure inversely correlated with the index of the variation range of cardiointervals, reflecting the lower adaptive potential of the heart rate regulation mechanisms. Conclusion. We have found regular changes in the regulation of heart rate in adolescents with hypertension, that can be taken as markers of its progressive development and used by clinicians to develop more personalized approaches to medication treatment.